1993
DOI: 10.1111/j.1365-2141.1993.tb03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19‐associated haemophagocytosis in Evans syndrome: aplastic crisis accompanied by severe thrombocytopenia

Abstract: A 36-year-old man who had been treated for Evans syndrome (ES) developed an aplastic crisis caused by acute human parvovirus B19 (HPV) infection. Profound thrombocytopenia (8.0 x 10(9)/l) followed with a sudden increase in platelet-associated IgG (PAIgG) (1376.9 ng/10(7) plts). Bone marrow examination revealed a considerable number of haemophagocytic histiocytes without any disturbance of megakaryopoiesis. To our knowledge this is the first case of aplastic crisis with virus-associated haemophagocytosis in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…Several case reports have indicated that B19 may cause variable degrees of thrombocytopenia [69,70] and idiopathic thrombocytopenic purpura [71]. B19 has infrequently been associated with other haematological manifestations, including transient erythroblastopenia of childhood [72], DiamondBlackfan anaemia [73] and haemophagocytic lymphohistiocytosis [74].…”
Section: Haematological Disordersmentioning
confidence: 97%
“…Several case reports have indicated that B19 may cause variable degrees of thrombocytopenia [69,70] and idiopathic thrombocytopenic purpura [71]. B19 has infrequently been associated with other haematological manifestations, including transient erythroblastopenia of childhood [72], DiamondBlackfan anaemia [73] and haemophagocytic lymphohistiocytosis [74].…”
Section: Haematological Disordersmentioning
confidence: 97%
“…Deve-se prestar particular atenção nas infecções intrauterinas por parvovírus B19, pois estas podem levar à hidropsia e morte fetal, sendo responsáveis por cerca de 16 % dos casos de hidropsia fetal não imune 6 . Em pacientes portadores de hemoglobinopatias, como doença falciforme e talassemias, ou defeitos da membrana eritrocitária, como na esferocitose hereditária, a parvovirose aguda pode desencadear crises aplásticas 2,[7][8][9][10][11] . A associação entre infecções por parvovírus B19 e HIV-1, produzindo aplasia pura de glóbulos vermelhos, também já foi descrita 12 .…”
Section: Introductionunclassified
“…B19 infection has been detected in cases of hemophagocytosis syndrome among children and adults (145,191,280,286,308,340,352; Toyoshige and Takahashi et al, Letter, Int. J. Hematol.…”
Section: Infection In the Immunodeficient Hostmentioning
confidence: 99%